Development of E-module Based on Science, Technology, Engineering, and Mathematics (STEM) To Improve Science Literacy of Junior High School Students - Hutomo, Bagus Addin; Saptono, Sigit; Subali, Bambang (Journal of Innovative Science Education, 2022)
In the 21st century, the development of science and technology is increasing rapidly, especially in the field of education. To prepare for these developments, students must be equipped with skills that support the use of technology and scientific literacy skills. The importance of scientific literacy skills in science learning is motivated by the results of the 2015 PISA test. The purpose of this study was to test the feasibility of STEM-based e-modules, analyze the effectiveness and profile of scientific literacy skills after using STEM-based e-modules. This research includes Research and Development (R&D) research from Borg & Gall in Sugiyono which has been modified without widespread dissemination. The data analysis technique used in this study includes descriptive data analysis related to the feasibility and profile of students' scientific literacy abilities, while the N-gain test is used to determine the effectiveness of the product. The results showed (1) the STEM-based (Science, Technology, Engineering, and Mathematics) e-module that was developed had very feasible criteria regarding aspects of content, presentation, and language (2) the results of the student's scientific literacy assessment showed an increase in the N-gain value with high criteria. (3) the profile of students' scientific literacy abilities which includes the process of science, the context of science, and the content of science have good criteria. Based on this, the use of the developed Science, Technology, Engineering and Mathematical (STEM)-based e-module is feasible to be used as an alternative learning resource for substance pressure material in science learning.